Processing Fresh-Cut Potatoes Using Non-Thermal Technologies and Edible Coatings - Christina Drosou; Ioannis Sklirakis; Ekaterini Polyzou; Iakovos Yakoumis; Christos J. Boukouvalas; Magdalini Krokida (Applied Sciences)
The increasing consumer demand for minimally processed and ready-to-cook food products has elevated the significance of fresh-cut potatoes, which offer health benefits, high sensory properties, and convenience. However, extending the shelf life of fresh-cut potatoes while preserving their organoleptic qualities remains a significant challenge. This review examines the effectiveness of emerging non-thermal technologies, such as osmotic dehydration (OD), high-pressure processing (HPP), pulsed electric field (PEF), and ohmic heating (OH), in processing fresh-cut potatoes. Among these, HPP and PEF have shown particular promise in extending shelf life and preserving sensory attributes, while OD and OH present advantages in maintaining nutritional quality. However, challenges such as high energy consumption, equipment costs, and industrial scalability limit their broader application. The use of natural preservatives and edible coatings is also explored as a means to enhance product quality and address the demand for clean-label foods. Further research is needed to optimize these technologies for large-scale production, reduce energy usage, and explore combined approaches for improved shelf life extension. This comprehensive review provides a critical analysis of the operational parameters of these technologies and their impact on the quality and shelf life of fresh-cut potatoes, identifying current research gaps and proposing directions for future studies.